Vermiost / Colleen Ineme Bernard J Dalinting ... [et al.] - Bernard J Dalinting, Colleen Ineme; Gelungan, Cynthia; Madi, Nabila Evianna; Benedict, Rachel; Ajat, Norainie (2011)
The name that we had chosen for our business is "Vermiost". We had chosen to do a business in worm composting that is known as vermicomposting. This type of business is related in the agricultural sector as well as waste management. This is because, the production of worm compost is done by utilizing various species of worms to create a heterogeneous mixture of decomposing vegetable or old newspapers, bedding materials, and vermicast(also known as worm compost).So by having this, we can continue on our nature of business that is the production and marketing ofvermicompost. Our business needs to be situated in a place where there are direct accesses to water source, electricity and tar roads to commence the business. Therefore, we had chosen a place in Sabah which the location is situated in Lahad Datu. We plan to acquire3 hectares of land in line with the planning of how much we want the production ofvermicompost to be. When all are prepared and taken care of, we would like to commence our business on the 11th of November 2011. There are several factors in selecting our business. Firstly, our business is new and innovative which can in tum attract customers and raise profits for our business quickly. Secondly, the source of input is at low cost as it is unwanted domestically. This means that the inputs, which are the wastes, can be collected easily and without much cost as it is usually unwanted stuffs. And lastly, the worms that are used to produce vermicompost propagate at a high rate, which enables production ofvermicompost to fulfill the rising demand on time. Given all this, we see our business prospect as to be bright due to several reasons. This is because, we can diversify the business into worm cultivation packing of vermicompost, trading of vermicompost, horticultural crops production that utilizes vermicompost, and agrotourism.